(3fRgI GdCdHGH GdLGeYI dafhf GdBOGHs - (3YHO Gddg Hf YHO Gddg Hf SdGeg GdCOcGhj GdTGaYj GdeYQha HGdeDPfs
(3ChdgG (B:s
(3MeOkG def Rjf eMGad GdNdaGA HeMGSf GdCOHGA, hCfgV gege dGcJSGH GdeYGdj, aGcJSHhG ef MddgG OjHGLkG ePgHkG s
(3BNQgG (B:s
(3ef GdHGH GdYTQjf hgh aj GdgRd hGdeLhf jJdhg GdfUa GdKGfj hgh ef GdHGH GdMGOj hGdYTQjf aj NHQ HYV GdeLGfjf hef aj eYfGge s
(3fSNI KGdKIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B138 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs